2019
DOI: 10.3390/metabo9020036
|View full text |Cite
|
Sign up to set email alerts
|

Function, Detection and Alteration of Acylcarnitine Metabolism in Hepatocellular Carcinoma

Abstract: Acylcarnitines play an essential role in regulating the balance of intracellular sugar and lipid metabolism. They serve as carriers to transport activated long-chain fatty acids into mitochondria for β-oxidation as a major source of energy for cell activities. The liver is the most important organ for endogenous carnitine synthesis and metabolism. Hepatocellular carcinoma (HCC), a primary malignancy of the live with poor prognosis, may strongly influence the level of acylcarnitines. In this paper, the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 137 publications
2
102
1
Order By: Relevance
“…Particularly, two studies showed higher levels of long-chain acylcarnitines and lower levels of medium and short-chain acyl-carnitines in HCC and serum of patients [ 154 , 161 ]. Acylcarnitine plays a central role in cellular lipid metabolism, as it is involved in the transport of activated LCFAs into mitochondria to sustain FAO [ 162 ]. The authors explain that the high ratio long-chain acylcarnitine/short-chain acylcarnitine is likely due to the high request of β-oxidation [ 154 ].…”
Section: Lipid Metabolic Reprogrammingmentioning
confidence: 99%
“…Particularly, two studies showed higher levels of long-chain acylcarnitines and lower levels of medium and short-chain acyl-carnitines in HCC and serum of patients [ 154 , 161 ]. Acylcarnitine plays a central role in cellular lipid metabolism, as it is involved in the transport of activated LCFAs into mitochondria to sustain FAO [ 162 ]. The authors explain that the high ratio long-chain acylcarnitine/short-chain acylcarnitine is likely due to the high request of β-oxidation [ 154 ].…”
Section: Lipid Metabolic Reprogrammingmentioning
confidence: 99%
“…The present study shows that NAGLU −/− mice had increased levels of BCAAs (Leu, Ile, and Val), Phe and Tyr amino acids, free carnitine, and acylcarnitines in both liver and heart tissue. The augmented levels of BCAAs concomitant with the accumulation of short-chain acylcarnitines (C3, C5), involved in BCAA metabolism [33,34], suggest an impaired catabolism of BCAAs in the liver and heart of MPS IIIB-affected mice. BCAA metabolism occurs in the liver; however, it is also active in other tissues, including the heart, adipose tissues, kidney, and skeletal muscle [35].…”
Section: Discussionmentioning
confidence: 99%
“…Carnitine also has an antioxidant and anti-inflammatory capacity [48,50]. Some studies have reported that acetyl-carnitine and carnitine are associated with liver function, liver diseases, neurologic disorders, and IBD [22,[51][52][53][54]. Therefore, liver damage due to intestinal inflammation occurs as a result of changes in the concentrations of acetyl-carnitine and carnitine.…”
Section: Discussionmentioning
confidence: 99%